2021
DOI: 10.3390/su13041964
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Framework of Smart Shipyard Maturity Level via Data Envelopment Analysis

Abstract: The fourth industrial revolution (“Industry 4.0”) has caused an escalating need for smart technologies in manufacturing industries. Companies are examining various cutting-edge technologies to realize smart manufacturing and construct smart factories and are devoting efforts to improve their maturity level. However, productivity improvement is rarely achieved because of the large variety of new technologies and their wide range of applications; thus, elaborately setting improvement goals and plans are seldom a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…18 Liesen et al 44 provided the technical approach and emphasized energy savings, implementation of energy efficiency measures in Portsmouth Naval Shipyard, and Jeong et al 45 described the power grid and the simulation of applying flywheel energy storage system on the power grid at the shipyard for shore power to ships and offshore facilities to save fuel consumption and reduce air emissions. In addition, the development of smart shipyards using data envelopment analysis has been shown by Woo et al 46 and the implementation of Industry 4.0 at shipyards using fuzzy AHP-TOPSIS hybrid method has been explained by Cil et al 47 The utilization of different types of renewable energy in shipyards has been investigated in various studies. Hadži c et al 48 identified the feasibility of investments in renewable energy systems for shipyards and the use of a photovoltaic power plant for a shipyard, and the potential of wave power parks for shipyards in Portugal was explored by Miglietta 49 and Neumann et al, 50 respectively.…”
Section: Of Operational Co 2 Emissionsmentioning
confidence: 99%
“…18 Liesen et al 44 provided the technical approach and emphasized energy savings, implementation of energy efficiency measures in Portsmouth Naval Shipyard, and Jeong et al 45 described the power grid and the simulation of applying flywheel energy storage system on the power grid at the shipyard for shore power to ships and offshore facilities to save fuel consumption and reduce air emissions. In addition, the development of smart shipyards using data envelopment analysis has been shown by Woo et al 46 and the implementation of Industry 4.0 at shipyards using fuzzy AHP-TOPSIS hybrid method has been explained by Cil et al 47 The utilization of different types of renewable energy in shipyards has been investigated in various studies. Hadži c et al 48 identified the feasibility of investments in renewable energy systems for shipyards and the use of a photovoltaic power plant for a shipyard, and the potential of wave power parks for shipyards in Portugal was explored by Miglietta 49 and Neumann et al, 50 respectively.…”
Section: Of Operational Co 2 Emissionsmentioning
confidence: 99%
“…Another research conducted a survey for the shipbuilding industry, investigating the adoption level of smart manufacturing and digital twins in eight shipyards from South Korea, proposing a new framework for smart shipyard maturity level assessment. Their results showed that adopting smart technologies for smart manufacturing led to better results than conventional methods [ 38 ].…”
Section: Introductionmentioning
confidence: 99%